Use of modern information and communication technologies in the process of preparation of future bachelors of motor transport - Ihor Vasilievich Hevko; Yuri Pavlovich Franko (Kazimierz Wielki University, 2020)
The importance of application of modern information technologies in the educational process of training future bachelors of road transport is outlined. It has been found that the use of computer tools makes the learning process more technological and effective. The focus is on the introduction of elements of computer-aided design in the educational process.